Survey-Based Analysis of Work Environment's Effect on Employee Stress at PT Indoneptune Manufacturing - Edwin Karim (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: The purpose of this study was to determine how much influence the work environment has on the work stress of netting employees at PT Indoneptune Manufacturing  Methodology: This research uses an associative quantitative approach by conducting a survey to the field. The population in this study were employees who worked at PT Indoneptune Manufacturing. Results: Work environment affects work stress Findings: That respondents are responding to the current working environment in the company to create a more comfortable working environment.. Novelty: The research uses the production section as the research sample. Originality: This study uses production employees as a sample to examine the effect of work environment on work stress. Conclusion: The researcher found that employees often leave due to illness, which is an indicator of work stress. Type of Paper: This paper is an empirical research paper.